Costs for Colon Cancer Treatment Comparing Benefit Types and Care Sources in the US Military Health System. Issue 11 (3rd April 2019) - Eaglehouse, Yvonne L; Georg, Matthew W; Richard, Patrick; Shriver, Craig D; Zhu, Kangmin
ABSTRACT: Introduction: Cancer is one of the leading causes of morbidity and mortality in the USA, contributing largely to US healthcare spending. Provision of services (direct or purchased) and insurance benefit type may impact cost for cancer care. As a common cause of cancer in both men and women, we aim to compare colon cancer treatment costs between insurance benefit types and care sources in the US Military Health System (MHS) to better understand whether and to what extent these system factors impact cancer care costs. Materials and Methods: Department of Defense Central Cancer Registry records and MHS Data Repository administrative claims were used to identify MHS beneficiaries aged 18–64 who were diagnosed with primary colon adenocarcinoma and received treatment between 2003 and 2008. The data linkage was approved by the Institutional Review Boards of the Walter Reed National Military Medical Center, the Defense Health Agency, and the National Institutes of Health. Costs to the MHS for each claim related to cancer treatment were extracted from the linked data and adjusted to 2008 USD. We used quantile regression models to compare median cancer treatment costs between benefit types and care sources (direct, purchased, or both), adjusted for demographic, tumor, and treatment characteristics. Results: The median per capita ( n = 801) costs for colon cancer care were 60, 321 (interquartile range 24, 625, 159, 729) over a median follow-up of 1.7 years. The model-estimated treatment costs were similar between benefit types. Patients using direct care had significantly lower estimated median costs [34, 145 (standard error 4, 326)] than patients using purchased care [106, 395 (10, 559)] or both care sources [82, 439 (13, 330)], controlled for patient demographic, tumor, and treatment characteristics. Differences in cost by care source were noted for patients with later stage tumors and by treatment type. Relative costs were 2–3 times higher for purchased care compared to direct care for patients with late-stage tumors and for patients receiving chemotherapy or radiation treatment. Conclusions: In the MHS, median cost for colon cancer treatment was lower in direct care compared to purchased care or patients using a combination of direct and purchased care. The variation in cancer treatment costs between care sources may be due to differences in treatment incentives or capabilities. Additional studies on cost differences between direct and purchased services are needed to understand how provision of care affects cancer treatment costs and to identify possible targets for cost reduction.